(untitled) (Bangladesh Agronomy Journal, 2015)
The experiment was conducted in the farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during the period from August to December 2012 to study the effect of various combinations of organic manure and inorganic fertilizer on the growth, yield, chlorophyll and nutrient content of rice var. BRRI dhan33. The treatment consists of T1: 100% Inorganic fertilizer (Recommended dose) + 5 ton poultry manure (PM) /ha , T2: 75 % N of recommended dose + 5 ton PM /ha, T3: 50 % N of recommended dose + 5 ton PM /ha, T4: 25 % N of recommended dose + 5 ton PM /ha, T5: 75 % S of recommended dose + 5 ton PM /ha, T6: 50 % S of recommended dose + 5 ton PM /ha, T7: 25 % S of recommended dose + 5 ton PM /ha, T8: 100% Inorganic fertilizer and T9: 5 ton PM /ha. Significant variation was found in growth and yield parameters as well as in chlorophyll content and nutrient content of aman rice. The most of the growth parameters ( plant height, leaf length and diameter, leaf number and total tiller plant-1) results were found better in 100% Inorganic fertilizer + 5 ton PM ha-1 which was statistically similar with 75 % of recommended dose of S + 5 ton PM ha-1, 75 % of recommended dose of N + 5 ton PM ha-1and followed by 50 % of recommended dose of S + 5 ton PM ha-1,respectively while the lowest from 5 ton/ha PM treatment. On the other hand, significantly higher chlorophyll a, b and total chlorophyll content were recorded in 100% Inorganic fertilizer + 5 ton PM ha-1and it was closely followed by 75 % of recommended dose of N + 5 ton PM ha-1 and lowest in 5 ton PM ha-1. Number of effective tillers plant-1, panicle length, number of rachis plant-1, filled grain plant-1 and fresh weight of plant were highest in 100% Inorganic fertilizer + 5 ton PM /ha and it was either statistically similar or closely followed by 75 % of recommended dose of S + 5 ton PM ha-1. Higher grain yield (4.18 t ha-1) was recorded in T1 which was statistically similar with T5 (4.13 t ha-1) whereas lowest grain yield (3.67 t ha-1) was from sole PM. Similarly, N content in grain and N, K content in straw were also showed similar trend. S content in grain and P, S content in straw were higher in 75 % of recommended dose of S + 5 ton PM /ha compared to other fertilizer treatments. Lowest N and S content in grain and N, P, K, S content in straw were found from the treatment using poultry manure only. Bangladesh Agron. J. 2015, 18(1): 99-111